2005
DOI: 10.1002/prop.200410215
|View full text |Cite
|
Sign up to set email alerts
|

Strings and D‐branes in holographic backgrounds

Abstract: We review recent progress in the study of non-rational (boundary) conformal field theories and their applications to describe exact holographic backgrounds in superstring theory. We focus mainly on the example of the supersymmetric coset SL(2, R)/U (1) , corresponding to the two-dimensional black hole, and its dual N=2 Liouville. In particular we discuss the modular properties of their characters, their partition function as well as the exact boundary states for their various D-branes. Then these results are u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…The issue of geometric cosets as exact backgrounds has been recently revisited in [5]. There, it was shown that S 2 ≡ SU (2)/U (1) and AdS 2 ≡ SL(2, R)/U (1) space , with magnetic and electric fluxes and no dilaton, can be obtained as extreme marginal deformations of the SU (2) k and SL(2, R)k wzw models.…”
Section: Motivations and Summarymentioning
confidence: 99%
See 4 more Smart Citations
“…The issue of geometric cosets as exact backgrounds has been recently revisited in [5]. There, it was shown that S 2 ≡ SU (2)/U (1) and AdS 2 ≡ SL(2, R)/U (1) space , with magnetic and electric fluxes and no dilaton, can be obtained as extreme marginal deformations of the SU (2) k and SL(2, R)k wzw models.…”
Section: Motivations and Summarymentioning
confidence: 99%
“…From this form of the deformed metric we see that there is a "natural" maximal value h a = 1/ √ 2 where the contribution of the J a ⊗ J a term changes its sign and the signature of the metric is thus changed. One could naively think that the maximal value h a = 1/ √ 2 can't be attained since the this would correspond to a degenerate manifold of lower dimension; what actually happens is that the deformation selects the the maximal torus that decouples in the h a = h → 1/ √ 2 limit as it was shown in [5] for the SU (2) and SL (2, R) algebras.…”
Section: Asymmetric Deformationsmentioning
confidence: 99%
See 3 more Smart Citations